Geotechnical Characterization and Random Field Modeling of Desiccated Clay - Stuedlein, Armin W; Kramer, Steven L; Arduino, Pedro; Holtz, Robert D (Journal of geotechnical and geoenvironmental engineering, 2012)
AbstractAn extensive set of in situ and laboratory test data is presented for a footing load test site east of Houston, Texas, in desiccated Beaumont clay. The in situ test program included standard and cone penetration tests (CPTs), the latter of which was selected for statistical analysis to produce vertical and horizontal random field model parameters for corrected cone tip resistance. Given the relatively high sampling frequency of the cone tip resistance in the vertical direction, the vertical random field model parameters were determined using the modified Bartlett’s test statistic with fitted autocorrelation models subject to a strict fitting criterion. Horizontal random field model parameters were generated by collapsing the two-dimensional distribution of the CPTs to a one-dimensional representation and by using less stringent evaluation of the autocorrelation. The results of this study indicate that Beaumont clay exhibits greater inherent spatial variability than previously reported at other clay sites, which is attributed to the secondary structure of the desiccated clay. A companion paper discusses the performance of a footing load test in the context of spatial and transformation uncertainty.